Germline Jak2-R1063H mutation interferes with normal hematopoietic development and increases risk of thrombosis and leukemic transformation - Zimolova, Veronika; Burocziova, Monika; Berkova, Linda; Grusanovic, Srdjan; Gursky, Jan; Janotka, Lubos; Kasparek, Petr; Pecinova, Alena; Kundrat, David; Hrckulak, Dusan; Onhajzer, Jakub; Jeziskova, Ivana; et al. (Leukemia, 2025)
The acquired JAK2-V617F mutation plays a causal role in myeloproliferative neoplasms (MPN). Weakly activating JAK2 germline variants have been associated with MPN risk, but the underlying mechanisms remain unclear. We previously identified the JAK2-R1063H germline variant, which contributes to hereditary MPN and increased disease severity in essential thrombocythemia. Here, we studied alterations in hematopoiesis in Jak2-R1063H knock-in mice. The Jak2-R1063H mouse cohort exhibited increased mortality, stimulated thrombopoiesis and elevated D-dimers levels, indicative of thrombotic complications. Bone marrow analysis revealed myeloid bias, enhanced megakaryopoiesis and activation of inflammatory signaling. Transcriptional and functional assays of hematopoietic stem cells suggested their accelerated aging and functional decline. The Egr1 transcriptional network, including the Thbs1 gene, progressively increased in aging mice, reinforcing alterations initiated by Jak2/Stat signaling. In murine acute myelogenous leukemia models, the Jak2-R1063H cooperated with a driver oncogene in promoting leukemogenesis. Germline JAK2-R1063H was found in 10 of 200 MPN patients from local hematology centers, with a higher minor allele frequency compared to healthy controls. Patients harboring JAK2-R1063H variant exhibited an increased incidence of thrombotic complications and disease progression with shortened survival. In conclusion, our findings identify the JAK2-R1063H germline variant as a risk factor for MPN development, thrombotic complications, and leukemic transformation. Our study, which involves a mouse model and a cohort of 200 MPN patients, characterizes the JAK2-R1063H germline mutation as a risk factor for MPN development, thrombotic complications, and leukemic transformation. These findings may have important clinical implications for managing MPN patients carrying the JAK2-R1063H germline variant.